From static to dynamic prosthodontics: digital recording of mandibular function for personalized prosthetic rehabilitation - Raghavan, Rohit; P. A., Shajahan; S. B., Shaman Shalu (International Journal of Research in Medical Sciences, 2026)
Conventional prosthodontic diagnosis and treatment planning rely extensively on static records such as diagnostic casts, maxillomandibular relationship records, facebow transfers, interocclusal records, and mechanical articulators. Although these methods remain clinically valuable, they provide only a limited representation of the continuously changing relationship between the maxilla, mandible, temporomandibular joints, dentition, and neuromuscular system. Advances in digital dentistry have enabled the acquisition of three-dimensional anatomical information together with patient-specific mandibular movement. Intraoral scanning, facial scanning, cone-beam computed tomography, digital maxillomandibular registration, optical jaw tracking, computerized occlusal analysis, and virtual articulation can now be combined to develop increasingly comprehensive digital representations of the prosthodontic patient. Incorporating movement into a three-dimensional virtual patient introduces a fourth dimension-time-and provides an opportunity to evaluate prosthetic designs under dynamic rather than purely static conditions. This transition may be particularly relevant to complete dentures, implant-supported prostheses, and extensive restorative rehabilitation. However, differences among acquisition systems, registration errors, limited standardization, equipment costs, and insufficient long-term clinical evidence currently restrict widespread implementation. This narrative review discusses the evolution from static to dynamic prosthodontic records, contemporary technologies for recording mandibular function, their integration with virtual articulation, and their potential contribution to personalized prosthetic rehabilitation. Emerging concepts including four-dimensional virtual patients, artificial intelligence-assisted movement analysis, and functional digital twins are also considered.